1982
DOI: 10.1093/infdis/146.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Role of Peptidoglycan from Staphylococcus aureus in Leukopenia, Thrombocytopenia, and Complement Activation Associated with Bacteremia

Abstract: The role of the major cell wall components of Staphylococcus aureus in the leukopenia, thrombocytopenia, and complement activation associated with S. aureus bacteremia was studied in a guinea pig model. Formalin-killed S. aureus strains HSmR, 52A5, Cowan I, and Cowan EMS and purified peptidoglycan were used. Normal animals given peptidoglycan developed early (5-min) leukopenia, thrombocytopenia, and depletion of C3-C9 hemolytic activity similar to values in animals given killed S. aureus organisms and C4-defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…In particular, SPA is best known for its ability to bind IgG (32), but can also bind other host factors, including von Willebrand's factor (33) and the VH3 receptor of B-cells (34). SPA also possesses antiphagocytic activity (35,36), and the ability to activate TNFR1 (37) and to induce apoptosis of naïve B cells (38). Purified protein A has been reported to be sufficient to stimulate CXCL8 production by lung epithelial cells and cause neutrophil recruitment in vivo.…”
Section: Chemokinementioning
confidence: 99%
“…In particular, SPA is best known for its ability to bind IgG (32), but can also bind other host factors, including von Willebrand's factor (33) and the VH3 receptor of B-cells (34). SPA also possesses antiphagocytic activity (35,36), and the ability to activate TNFR1 (37) and to induce apoptosis of naïve B cells (38). Purified protein A has been reported to be sufficient to stimulate CXCL8 production by lung epithelial cells and cause neutrophil recruitment in vivo.…”
Section: Chemokinementioning
confidence: 99%
“…A number of studies suggest that the bacterial component peptidoglycan (PepG) may contribute to this fatal condition (14,35,44,49). PepG may reach the circulation by translocation from the intestine and by bacterial breakdown during gram-positive infections (25,33,37).…”
mentioning
confidence: 99%
“…Human complement factor C5a, one of the split products of complement activation, is known to induce TNF release from monocytes in vitro [27] and to enhance TNF release induced in vivo in the presence of endotoxin or whole S. epidevmidis bacteria [4]. Furthermore, Spika et al [28] found that PG from S. aweus strains contributes to complement activation and the induction of leukopenia and thrombocytopenia. The observation that both C1 and C3/C4 depletion, as well as heat inactivation of the serum, diminished the serum-enhanced TNF release induced by PG indicates that the enhancement is mediated mainly by the activation of the classical complement pathway.…”
Section: Discussionmentioning
confidence: 99%